A demographic headwind: Will an aging society reduce the real interest rate and potential growth? - Emerson, Patrick; Knabb, Shawn (Elsevier B.V., 2020)
Is secular stagnation a necessary result of population aging? This paper argues that demographic change itself is not enough to generate both slower economic growth and a lower real interest rate in an endogenous growth model with overlapping generations and human capital. It is then shown that the introduction of intergenerational transfer programs, specifically those that invest in public education and transfer resources to the elderly, can generate these dual observations. In fact, the existence of a pay-as-you-go government transfer program to the elderly is a necessary condition for both of these results to hold in our framework. We also demonstrate that how a society chooses to fund additional transfers to the elderly will determine the amount of 'drag' demographic factors might place on the economy. If a society chooses to reduce public spending on productive investments in children to fund transfers to the elderly, then the growth effect can be relatively large and exacerbate the downward pressure on the real interest rate. That is, the strength of the demographic headwind depends critically on whether or not redistribution to the elderly will crowd out investment in children.
Keywords: Population aging; Demographic headwind; Slow growth; Declining real interest rate